2001
DOI: 10.1007/s004420000539
|View full text |Cite
|
Sign up to set email alerts
|

Monsoonal influences on evapotranspiration of savanna vegetation of northern Australia

Abstract: Data from savannas of northern Australia are presented for net radiation, latent and sensible heat, ecosystem surface conductance (G ) and stand water use for sites covering a latitudinal range of 5° or 700 km. Measurements were made at three locations of increasing distance from the northern coastline and represent high- (1,750 mm), medium- (890 mm) and low- (520 mm) rainfall sites. This rainfall gradient arises from the weakened monsoonal influence with distance inland. Data were coupled to seasonal estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 55 publications
4
68
0
Order By: Relevance
“…Dry periods during the vegetative season in natural forests of higher latitudes neither bring about a decrease of transpiration (Goulden et al, 1997;Tchebakova et al, 2002). In contrast, transpiration of open ecosystems like savannas, grasslands or shrublands incapable of maintaining high soil moisture content year round, drops radically during the dry season (Hutley et al, 2001;Kurc and Small, 2004). Change of soil moisture content with time, dW/dt, is linked to precipitation P , evaporation E and runoff R via the law of matter conservation, dW/dt=P −E−R.…”
Section: Biotic Pump Of Atmospheric Moisturementioning
confidence: 98%
“…Dry periods during the vegetative season in natural forests of higher latitudes neither bring about a decrease of transpiration (Goulden et al, 1997;Tchebakova et al, 2002). In contrast, transpiration of open ecosystems like savannas, grasslands or shrublands incapable of maintaining high soil moisture content year round, drops radically during the dry season (Hutley et al, 2001;Kurc and Small, 2004). Change of soil moisture content with time, dW/dt, is linked to precipitation P , evaporation E and runoff R via the law of matter conservation, dW/dt=P −E−R.…”
Section: Biotic Pump Of Atmospheric Moisturementioning
confidence: 98%
“…The soils are well drained with a surface texture commonly of sandy loam changing to sandy clays and clay subsoils deeper than 1-1.5 m with a massive and earthy structure (Hutley et al, 2000(Hutley et al, , 2001. The vegetation consists of open forests and wetlands.…”
Section: The Study Catchmentmentioning
confidence: 99%
“…In savanna communities near Darwin, at the northern end of the precipitation gradient, the soil water that accumulates during the wet season is sufficient to maintain transpiration rates at constant, or even higher, rates in savanna eucalypts throughout the dry season compared to rates in the wet season Hutley et al, 2000Hutley et al, , 2001O'Grady et al, 1999). Measurements of predawn water potential suggested that these trees have access to available water even at the end of the dry season, presumably from roots that extend to several meters depth in the soil profile Hutley et al, 2000).…”
Section: Introductionmentioning
confidence: 99%